2022
DOI: 10.1039/d1qm01635k
|View full text |Cite
|
Sign up to set email alerts
|

Water-responsive shape memory thermoplastic polyurethane scaffolds triggered at body temperature for bone defect repair

Abstract: Combining selective laser sintering (SLS) and water-responsive shape memory polymer triggered at body temperature is highly promising for the accomplishment of bone defect repair with the approach of minimally invasive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 74 publications
0
17
0
Order By: Relevance
“…The cell proliferated over time, and there was no statistical difference among the groups after 4 days. However, the number of cells after 7 days showed the following order: Fe–Cu > Fe–CuO > Fe, suggesting that the incorporation of Cu favors the proliferation of MG-63 cells and vitality of cells with no cytotoxicity …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The cell proliferated over time, and there was no statistical difference among the groups after 4 days. However, the number of cells after 7 days showed the following order: Fe–Cu > Fe–CuO > Fe, suggesting that the incorporation of Cu favors the proliferation of MG-63 cells and vitality of cells with no cytotoxicity …”
Section: Resultsmentioning
confidence: 98%
“…However, the number of cells after 7 days showed the following order: Fe−Cu > Fe−CuO > Fe, suggesting that the incorporation of Cu favors the proliferation of MG-63 cells and vitality of cells with no cytotoxicity. 52 Previous studies have demonstrated that the toxicity of metal implants arises from the metallic ions and oxide or hydroxide layer. 53,54 The higher viabilities in Fe−Cu and Fe−CuO samples than in pure Fe indicates that the cell activity is improved by the degradation products, resulting from the Cu ions released during the degradation.…”
Section: Cytocompatibility Evaluationmentioning
confidence: 99%
“…The representative PLLA/Fe 3 O 4 @SiO 2 scaffold with honeycomb structure was fabricated via SLS technology. In detail, the PLLA/Fe 3 O 4 @SiO 2 powders were paved on the powder bed and selectively laser scanned according to the designed three-dimensional model, with laser power at 2.5 W, scanning speed at 100 mm/s and scanning distance at 0.24 mm [ 20 , 21 ]. The modeling platform gradually descended with each layer of powders was sintered until the scaffold was completely formed.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…Meanwhile, the formed nanocomposites also demonstrate many excellent collective properties, such as enhanced light absorption, declined recombination of electron–hole pairs, and so on . Recently, two-dimensional (2D) nanomaterials as photosensitizers have attracted extensive attention of researchers because of their large surface area and distinct optical properties. , Among them, graphitic carbon nitride (g-C 3 N 4 , CN) nanosheets, as a 2D metal-free photosensitizer, have been widely reported on the aspect of photodynamic anti-infection due to their excellent biocompatibility, moderate band gap (2.7–2.8 eV), and good stability . Bismuth sulfide (Bi 2 S 3 ) nanorods, as a binary metal sulfide, are superior photothermal nanoparticles, which are widely utilized in antibacterial and antitumor studies because of their good biocompatibility, high photothermal conversion efficiency, and physicochemical stability .…”
Section: Introductionmentioning
confidence: 99%